The Influence of Competence, Learning Methods, Infrastructure Facilities on Graduate Quality (Case Study (Vocational High School) SMKN 5 Bandung Indonesia) - Mina Nurliana; Bambang Sudaryana (Universitas Djuanda, 2020)
The main objective of this research is to determine teacher competency requirements that support appropriate learning methods and be able to increase students' high learning desires and establish good learning facilities to determine the achievement of quality graduates and love knowledge. This study is expected to investigate how competencies, learning methods and ideal learning infrastructure can be used to improve students' understanding and comfort of teaching and learning processes that support intellectual quality and love knowledge. This notion arose after discovering that teaching practices for the affective domain were ineffective. Students learn to pass examinations, not to love knowledge. Experiments are conducted for 1 (one) year or 2 semesters, in January - December 2019, to determine the impact of learning experiences on students' academic achievement. The research sample consisted of 10 English teachers and 20 students from the Vocational High School. The students are divided into two groups; the control group (10 students) and the experimental group (10 students). Both groups were taught the same topic and learning objectives for 2 hour. However, the control group was taught using lecture slides, group discussions and closed with a question and answer session. Meanwhile, the experimental group is taught using new instructional instruments that adapt learning experiences that are appropriate to the curriculum. During the teaching session, the teacher observes student participation in all their activities and behavior during the lesson session. To complete this study, tests are conducted to see the impact of the learning experience on students' academic achievement.